Study on Tim3 Regulation of Multiple Myeloma Cell Proliferation via NF-κB Signal Pathways - Liu, Zhaoyun; Xiang, Chenhuan; Han, Mei; Meng, Nanhao; Luo, Jingyi; Fu, Rong (Frontiers in Oncology, 2020)
Objective As an important negative regulatory factor of immunological cells, Tim3 plays a regulating role in tumor immune microenvironment. The purpose of this study was to investigate the expression of Tim3 on MM cells and its effect on the proliferation and apoptosis of MM cells, as well as its potential mechanism. Methods In this study, the expression of Tim3 was detected on myeloma cells (CD38+CD138+ cells) of bone marrow by flow cytometry (FCM) from 167 patients with MM and 51 healthy donors as controls and making correlation analysis with related clinical indexes. In vitro, MM cell lines (RPMI-8226 and U266) were treated with Tim3 knock-down alone, bortezomib alone and combination of Tim3 knock-down and bortezomib, then cell proliferation, cell apoptosis and downstream signaling pathway were detected by CCK-8, FCM, RT-PCR and western blot. Results The expression of Tim3 on myeloma cells in MM patients was significantly higher than normal control group and positively correlated with β2 microglobulin, creatine, and plasma cells of bone marrow, negatively correlated with hemoglobin and red blood cells. In vitro, we validated the high expression of Tim3 in RPMI-8226 and U266 cell lines. After Tim3 knock-down, the cell proliferation was inhibited and cell apoptosis was induced, the relative mRNA and protein expression of Tim3 and NF-κB signal pathway (PI3K, AKT, mTOR, NF-κB) were significantly decreased. Also, the cell proliferation was inhibited, cell apoptosis was increased, the relative mRNA and protein expression of NF-κB were decreased significantly in combination group than bortezomib or Tim3 knock-down group. Conclusions The high expression of Tim3 on MM cells is associated with progression of MM patients. Tim3 maybe regulate the proliferation of MM cells via NF-κB signal pathway. Down-regulation of Tim3 expression can inhibit proliferation and induce apoptosis of MM cells, also has an additive inhibitory effect of bortezomib on NF-κB signaling pathway, then inhibit proliferation and induce apoptosis. Therefore, Tim3 may be a potential target for the treatment of MM.